Anemia in patients with tumors of the female reproductive system - A. G. Kedrova; T. A. Greyan; N. S. Vanke; S. E. Krasilnikovт (Опухоли женской репродуктивной системы)
Objective: to assess the efficacy of Sideral forte (combination of sucrosomial iron and vitamin C) in the treatment of iron deficiency anemia in patients with tumors of the female reproductive system.Materials and methods. The study included 35 patients with benign tumors of the female reproductive system and 27 patients with cancer; all of them were also diagnosed with grade I iron deficiency anemia. The duration of therapy with Sideral forte at a dose of 1 capsule per day varied between 30 and 60 days. We evaluated frequency and intensity of clinical and hematological response to treatment, as well as drug tolerability.Results. Therapy with Sideral forte ensured improvement of blood parameters in both patient groups. All participants received the drug during 8 weeks; it was well tolerated, demonstrated no side effects, and did not cause gastrointestinal disorders. The increase in the level of hemoglobin was observed in both groups; however, cancer patients had less pronounced dynamics.Conclusions. Sideral forte is an effective oral drug that can be used for the treatment of iron deficiency anemia in patients with tumors of the female reproductive system.